Dietary Protein, Vitamin C, and Iron Intake As Predictors of Hemoglobin Levels in Children With Special Needs” - Yoni Astuti; Sunarti Sunarti; Gina Puspita; Iman Permana (CV. Inara, 2026)
Hemoglobin (Hb) is a key indicator of oxygen transport and overall child health, particularly during periods of rapid growth and cognitive development. Anemia remains a significant global public health problem, often driven by nutritional deficiencies, especially iron. Vitamin C enhances iron absorption, while protein supports hemoglobin synthesis, indicating a synergistic role of these nutrients. Children with special needs are at higher risk of nutritional inadequacies due to feeding challenges and restricted diets. However, evidence on how dietary intake influences hemoglobin levels in this population is still limited. Aims:This study aimed to analyze the role of dietary protein, vitamin C, and iron intake as predictors of hemoglobin levels in children with special needs. Methods:A cross-sectional observational study was conducted among 34 students at SLB Kutoarjo between January and May 2024. Dietary intake data were collected using a 3-day food record completed by caregivers and analyzed with NutriSurvey software. Hemoglobin data were obtained from school health records. Statistical analysis included correlation and multiple regression tests to assess the relationship between nutrient intake and hemoglobin levels. Results:The findings revealed that the average intake of protein, iron, vitamin C, and total energy was below recommended levels. Despite this, the mean hemoglobin level (13.38 ± 1.33 g/dL) was within the normal range. Regression analysis showed that the combined intake of protein, iron, vitamin C, and folate explained 25% of the variation in hemoglobin levels (R² = 0.25), but the adjusted R² was low (0.036), indicating weak explanatory power. No individual nutrient showed a statistically significant association with hemoglobin levels (p > 0.05). Conclusions:Dietary protein, vitamin C, and iron intake were not significant predictors of hemoglobin levels in children with special needs. These findings highlight that hemoglobin status is influenced by complex interactions beyond dietary intake alone. Further research with larger samples and additional biomarkers is needed to better understand anemia risk in this population.